Mapping of Female Breast Cancer Incidence and Mortality Rates to Socioeconomic Factors Cohort: Path Diagram Analysis - Peng, Qiongle; Ren, Xiaoling (Frontiers in Public Health, 2022)
Comparisons of incidence and mortality rates of female breast cancer are useful approaches to define cancer-related socioeconomic disparities. This was a retrospective observational cohort study on breast cancer of females in several developed countries over thirty years. The he effects of socioeconomic factors were analyzed using path diagram method. Results showed that the relationship between socioeconomic factors and the occurrence and development of breast cancer did not follow a monotonic function. We found a positive, significant association of national public wealth on the incidence and mortality of breast cancer, and the path coefficients in the structural equations model are -0.51 and -0.39, respectively. The unemployment rate is critical for the incidence and mortality, and the path coefficients are all 0.2. The path coefficients of individual economic wealth to the rates of breast cancer is 0.18 and 0.27, respectively. The influence of social pressure on the incidence and mortality of breast cancer was not typical monotonous. The survival rate of breast cancer determined by the ratio of mortality rate to incidence rate also showed a similar pattern with socioeconomic factors.